Green supply chain management adoption in Lebanese manufacturing industries: an exploratory study. Issue 3 (2019) - Saade, Richard; Thoumy, Mira; Sakr, Omar
This paper bases itself on the dual factor theory to study the motivators, barriers and hygiene factors affecting the adoption of green supply chain management (GSCM) activities in Lebanese manufacturing industries. Out of 60 Lebanese companies that have already taken green initiatives, 37 were analysed. The paper reveals that GSCM adoption is positively correlated with marketing opportunities, market motivators and manpower's involvement. We also found that the external stakeholder's pressure and the lack of government support hinder the GSCM adoption. Moreover, ISO 14001 certified companies have shown a higher rate of adoption of GSCM.